Quality culture boosts agile transformation—Action research in a business‐to‐business software business. Issue 1 (29th August 2022) - Saarikallio, Matti; Tyrväinen, Pasi
Abstract: Agile methodologies are sometimes adopted, with the assumption that benefits can be attained by only using a set of best practices, which can sometimes work to a degree. In this paper, a case is discussed where a software‐producing organization of seven teams achieved significant improvements. The goal of the research was to answer two questions: how an already agile organization could improve its performance further and what is the impact of promoting quality aspects? The questions were answered by implementing interventions based on prior literature and data emerging from semi‐structured interviews. The context was an established business with a complex revenue stream structure, meaning the mix of various project/service/product based work rendered the adoption of agile methods a challenge. Action research comprising three rounds of interventions was conducted to improve the organization and its quality culture while enforcing code review practices. Interventions resulted in a significant improvement in quality, as measured by reported defects. Therefore, it is suggested that agile methods are not sufficient on their own to take software business forward unless a quality‐focused culture is simultaneously achieved through a mindset change and organizational structures to enforce quality practices. The paper contributes to research on the managerial practices of software business and agile transformation by providing empirical support to introducing formal quality improvement to the agile mix as a method for practitioners to improve organizations with complex business models and multiple teams. Abstract : Agile transformations tend to ignore accompanying implementation of software quality or it is considered a developer skill rather than organizational practice. This paper presents an empirical investigation of improving a multi‐team organization. It is demonstrated that significant software defect reduction is possible with small quality related cultural and procedural changes. Further, it is suggested that existing agile organizations with complex business models can enhance performance through quality improvements.